(Patho‐)physiological relevance of PINK1‐dependent ubiquitin phosphorylation. (14th July 2015) - Fiesel, Fabienne C; Ando, Maya; Hudec, Roman; Hill, Anneliese R; Castanedes‐Casey, Monica; Caulfield, Thomas R; Moussaud‐Lamodière, Elisabeth L; Stankowski, Jeannette N; Bauer, Peter O; Lorenzo‐Betancor, Oswaldo; Ferrer, Isidre; Arbelo, José M; et al.
Abstract Mutations in PINK1 and PARKIN cause recessive, early‐onset Parkinson's disease (PD). Together, these two proteins orchestrate a protective mitophagic response that ensures the safe disposal of damaged mitochondria. The kinase PINK1 phosphorylates ubiquitin (Ub) at the conserved residue S65, in addition to modifying the E3 ubiquitin ligase Parkin. The structural and functional consequences of Ub phosphorylation (pS65‐Ub) have already been suggested from in vitro experiments, but its (patho‐)physiological significance remains unknown. We have generated novel antibodies and assessed pS65‐Ub signals in vitro and in cells, including primary neurons, under endogenous conditions. pS65‐Ub is dependent on PINK1 kinase activity as confirmed in patient fibroblasts and postmortem brain samples harboring pathogenic mutations. We show that pS65‐Ub is reversible and barely detectable under basal conditions, but rapidly induced upon mitochondrial stress in cells and amplified in the presence of functional Parkin. pS65‐Ub accumulates in human brain during aging and disease in the form of cytoplasmic granules that partially overlap with mitochondrial, lysosomal, and total Ub markers. Additional studies are now warranted to further elucidate pS65‐Ub functions and fully explore its potential for biomarker or therapeutic development.